Les clôtures symboliques des Algériennes: la virginité ou l'honneur social en question - FERHATI, Barkahoum (Clio. Femmes, Genre, Histoire, 2007)
Liée à l'honneur de la famille, la virginité est une question qui a toujours hanté l'esprit des jeunes filles algériennes. Toutes sortes de pratiques sont envisagées par la société pour la préserver. La plus connue est celles du rbat (action de nouer), dit teskar (action de fermer) ou encore tesfah (action de blinder). Au moyen de techniques ritualisées, elle consiste en la « fermeture » symbolique de l'hymen avant la puberté et son « ouverture » symbolique la veille du mariage. La « chemise tachée du sang de la vierge » doit en être la preuve indéniable: elle authentifie que l'honneur de la famille, du groupe, est intact. Lorsque, pour diverses raisons, l'hymen fait défaut, la société déploie toutes sortes de stratégies palliatives. Aujourd'hui, le certificat de virginité et la reconstitution de l'hymen par la chirurgie plastique, l'hyménorrapie ou l'hyménoplastie, viennent renforcer la pratique symbolique du rabt. La question fondamentale que je pose dans cet article est: peut-on envisager de casser la clôture « malléable » de cette « vaste prison » des femmes afin que les Algériennes puissent intégrer la société en tant qu'individus et non en tant qu'emblèmes de l'honneur de la famille?
Keywords: afrique; algérie; anthropologie; approches et analyses; corps; cours; discipline; féminisme islamique; histoire; hymen; patriarcat; premier cycle; rapports sociaux de sexe; ressource en ligne; rituel; régions géographiques; sciences humaines; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; virginité

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences

Governing women's morality: a study of Islamic veiling in Canada - Atasoy, Y. (EUROPEAN JOURNAL OF CULTURAL STUDIES, 2006)
The veiling of Muslim women is subject to strongly contested ideas about whether the veil is a symbol of women's subordination to an oppressive tradition or a means of emancipation from that tradition. This article suggests that women's own personal reasons for veiling must be analysed. Data collected from published documents from Muslim organizations allows for demonstration that the veil is configured as central to an Islamic moral code of female modesty. A further analysis of findings from interviews conducted with veiled Muslim women in Winnipeg shows the nuanced ways in which women enact this code.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; corps; cours; discipline; féminisme islamique; histoire et politique; identité; manitoba; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; winnipeg

Attitudes Toward Victims of Rape: Effects of Gender, Race, Religion, and Social Class - Nagel, Barbara; Matsuo, Hisako; McIntyre, Kevin P.; Morrison, Nancy (Journal of Interpersonal Violence, 2005)
Although previous literature focusing on perceptions of victims of rape has examined how gender, race, and culture influence the attitudes one holds toward victims, these studies have yielded mixed results. This study compared perceptions of victims of rape across a wide range of ages, educational backgrounds, religions, and income levels, while focusing on gender and racial differences. Results indicate (N = 220) that victims of rape are generally viewed more sympathetically by females than by males and by Whites than by African Americans. However, the effect of race disappears when socioeconomic variables are controlled, suggesting a more complex relationship. Also, a hierarchical regression indicates that age, sex, education, and income are significant predictors of attitudes toward victims. This study builds on existing research that examines such attitudes from a cultural perspective and extends this literature by examining the interactive effects of several demographic variables within a community sample.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; viol; violences; états-unis

The female circumcision controversy: an anthropological perspective - Gruenbaum, Ellen (University of Pennsylvania Press, 2001)
To the Western eye, there is something jarringly incongruous, even shocking, about the image of a six-year-old girl being held down by loving relatives so that her genitals can be cut. Yet two million girls experience this each year. Most Westerners, upon learning of the practice of female circumcision, have responded with outrage; those committed to improving the status of women have gone beyond outrage to action by creating various programs for "eradicating" the practice. But few understand the real life complexities families face in deciding whether to follow the traditional practices or to take the risk of change. InThe Female Circumcision Controversy, Ellen Gruenbaum points out that Western outrage and Western efforts to stop genital mutilation often provoke a strong backlash from people in the countries where the practice is common. She looks at the validity of Western arguments against the practice. In doing so, she explores both outsider and insider perspectives on female circumcision, concentrating particularly on the complex attitudes of the individuals and groups who practice it and on indigenous efforts to end it. Gruenbaum finds that the criticisms of outsiders are frequently simplistic and fail to appreciate the diversity of cultural contexts, the complex meanings, and the conflicting responses to change. Drawing on over five years of fieldwork in Sudan, where the most severe forms of genital surgery are common, Gruenbaum shows that the practices of female circumcision are deeply embedded in Sudanese cultural traditions-in religious, moral, and aesthetic values, and in ideas about class, ethnicity, and gender. Her research illuminates both the resistance to and the acceptance of change. She shows that change is occurring as the result of economic and social developments, the influences of Islamic activists, the work of Sudanese health educators, and the efforts of educated African women. That does not mean that there is no role for outsiders, Gruenbaum asserts, and she offers suggestions for those who wish to help facilitate change. By presenting specific cultural contexts and human experiences with a deep knowledge of the tremendous variation of the practice and meaning of female circumcision, Gruenbaum provides an insightful analysis of the process of changing this complex, highly debated practice.
Section: 242 p. ; 23 cm
Keywords: afrique; anthropologie; approches et analyses; corps; cours; discipline; histoire et politique; justice sociale; point de vue situé; premier cycle; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; soudan; système colonial; systèmes d'oppressions; thématiques; violences

Corps, sexe et art: dimension symbolique - Pearl, Lydie (L'Harmattan, 2001)
Les années 60 marquent le début d'un art éphémère dans lequel l'objet d'art disparaît au profit d'une mise en scène du corps. Les Actionnistes viennois mêlent des corps féminins ou masculins dans la boue, du sang et des organes animaux etc. Comment ce qui peut paraître aberration ou perturbation de la personnalité est souvent une mise en scène microcosmique des idéologies ou des réalités politiques d'une époque : images d'une coupure Est/Ouest, de frontières infranchissables à l'époque de la guerre froide ou, au contraire, effacement des frontières au temps de la mondialisation avec des artistes de la Scène internationales
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; anthropologie; approches et analyses; art contemporain; arts; corps; cours; discipline; har4600; histoire de l'art; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sexualité; thématiques

Marché au sexe - Rubin, Gayle; Butler, Judith P.; Sokol, Eliane (EPEL, 2001)
"Aucun amateur de cuisine épicée ne se verra privé de liberté ou victime d'ostracisme pour avoir satisfait ses papilles gustatives. En revanche, on peut être jeté en prison pour trop aimer les chaussures en cuir. De même, l'homosexualité, le sida, la pornographie, le transsexualisme, et aujourd'hui la pédophilie, donnent-ils lieu à ce que Gayle Rubin appelle une " panique sexuelle ". Chaque panique désigne une minorité sexuelle, généralement inoffensive, comme population-cible. Au terme du processus, celle-ci se trouve décimée, et la société tout entière, juridiquement et socialement, réorganisée. Gayle Rubin a jeté les bases d'un champ autonome d'études sur le sexe où désir, jouissance et diversité érotique, pourraient trouver leur raison théorique et politique. Les trois textes publiés ici s'inscrivent dans une filiation politique (le féminisme, la nouvelle gauche, les luttes antiracistes, les luttes pour les droits civiques) et théorique (les sexologues, Freud, Lacan, Marx, Foucault, Derrida). Les paradigmes ne valent rien sans l'enquête de terrain, et rien non plus s'ils ne s'actualisent en choix de stratégie et de tactique politiques. L'ensemble s'éclaire du partiel, le partiel de l'ensemble. Nous sommes loin ici du communautarisme béat qu'on prête parfois en France aux intellectuels américains. Qu'on lise les critiques acerbes de Judith Butler sur les replis identitaires : les lesbiennes n'ont rien d'autre en commun que leur expérience du sexisme et de l'homophobie. Ou ses réserves sur le coming out : " La sexualité reste-t-elle sexualité quand elle est soumise à un critère de transparence et de révélation? Une quelconque sexualité serait-elle possible sans cette opacité qui a pour nom inconscient? " Gayle Rubin et Judith Butler soulignent constamment la nécessité de ne pas troquer une violence contre une autre, une démonologie religieuse contre une démonologie laïque, laissant ainsi sa chance à l'érotologie moderne. (Éditeur).
Contenue: Entretien : Marché au sexe / Gayle S. Rubin et Judith Butler – Penser le sexe / Gayle S. Rubin – Imitation et insubordination du genre / Judith Butler.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; corps; cours; cycles supérieurs; discipline; fem1000; fem7000; hétérosexisme; identités LGBTQIA2+; lesbianisme; lit3220; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex3383; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques; théories féministes; transféminisme; états-unis